2012
DOI: 10.1038/pr.2012.6
|View full text |Cite
|
Sign up to set email alerts
|

Preterm neonates show marked leukopenia and lymphopenia that are associated with increased regulatory T-cell values and diminished IL-7

Abstract: IntroductIon: current advances in neonatology have improved survival among preterm and low-birth-weight infants. however, the risk of neonatal death in preterm infants is much greater than in full-term neonates and is frequently associated with infections. Methods: Little is known about the immune status of preterm neonates; therefore, we analyzed the frequency and absolute counts of different immune populations in 211 cord blood samples taken from very-preterm to full-term neonates. results: We found that abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
55
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 42 publications
9
55
2
1
Order By: Relevance
“…This is consistent with the differences reported between premature and term infants at birth8 9 13 16 as well as in previous preterm infant longitudinal studies 20 22. Berrington et al 22 reported lower total lymphocyte count, T cells, B cells and T helper cells at 2 months of age in 18 preterm infants compared with term infants; some of these populations (total lymphocytes, T cells and T helper cells) remained significantly lower at their final sample at 6 months of age.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is consistent with the differences reported between premature and term infants at birth8 9 13 16 as well as in previous preterm infant longitudinal studies 20 22. Berrington et al 22 reported lower total lymphocyte count, T cells, B cells and T helper cells at 2 months of age in 18 preterm infants compared with term infants; some of these populations (total lymphocytes, T cells and T helper cells) remained significantly lower at their final sample at 6 months of age.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies analysed cord blood samples, and it may be that any significant effect of antenatal steroids had resolved by 2 months of age 8 13…”
Section: Discussionmentioning
confidence: 99%
“…This maternal alloantigen stimulus explains the presence of a high percentage of Treg in CB in early preterm (29w) compared to full term infants [33,34,37]. Treg prevalence then gradually decreases with GA, reaching a stable number at birth [34,37]. In our study, Treg frequencies did not differ significantly between moderate/late preterm and term neonates.…”
Section: Discussionmentioning
confidence: 42%
“…During fetal life a substantial number of maternal cells cross the placenta to reside in lymphoid tissues, inducing the development of Treg that keep maternal-fetal tolerance [35,36]. This maternal alloantigen stimulus explains the presence of a high percentage of Treg in CB in early preterm (29w) compared to full term infants [33,34,37]. Treg prevalence then gradually decreases with GA, reaching a stable number at birth [34,37].…”
Section: Discussionmentioning
confidence: 99%
“…Preterm infants are highly susceptible to invasive infections, which are leading causes of mortality and longterm morbidity. Treg levels and gestational age inversely correlated in several studies [48][49][50]. Preterm infants have higher Treg levels than full-term newborns.…”
Section: Circulating T Cells In the Fetus And Neonate Are Fundamentalmentioning
confidence: 97%